Radiographic and histologic evaluation of platelet-rich plasma and bovine-derived xenograft combination in bilateral sinus augmentation procedure - (:unkn) unknown (TAYLOR & FRANCIS INC, 2013)
There is currently a great interest regarding the use of platelet-rich plasma (PRP) in combination with various bone graft materials in sinus lift procedures. The purpose of this study was to assess and compare the radiographic and histological results of sinus augmentation procedures following treatment with PRP/bovine-derived xenograft (BDX) vs. BDX/collagen membrane. Using a split mouth design, 10 patients, with <= 5mm of residual alveolar bone in the vertical direction, were treated with PRP/BDX or BDX/collagen membrane. At 8 months after surgery, both graft materials led to a satisfactory increase in vertical dimensions of bone. Bone biopsies were taken from the augmented sites during the implant placement. Histological analysis demonstrated that majority of the trabecula contained orderly layered lamellar bone in the PRP/BDX group, whereas mainly woven bone with a haphazard arrangement of collagen fibers were noticed in the BDX/collagen membrane group. It can be concluded that both combinations resulted with a satisfactory bone height, but more prominent and mature bone formation was observed at sites treated with PRP/BDX.
Keywords: Platelet-rich plasma; bovine-derived xenograft; sinus floor augmentation; bone regeneration; GUIDED TISSUE REGENERATION; INTRABONY PERIODONTAL DEFECTS; BETA-TRICALCIUM PHOSPHATE; BONE BIO-OSS; FLOOR AUGMENTATION; AUTOGENOUS BONE; LIFT AUGMENTATION; SURVIVAL RATES; GROWTH-FACTOR; MAXILLARY